Factores biosociales laborales y nivel de estrés en enfermedades de áreas críticas - Calle Morales, Veronica De Jesús (2016)
This search is a quantitative, descriptive and correlational study, was conducted during the months of April 2010 to June 2011 in order to determine the relationship between biosocial factors, labor and stress level of nurses in the Critical Areas HRDT Trujillo – 2011. The sample consisted of 36 nurses working in critical areas of the Trujillo is Regional Teaching Hospital. For data collection instruments were used 02: The first known survey format Biosocial Factors and Labour, which was adapted and the second one called "The Nursing Stress Scale (NSS). The data were processed following a pattern and statistical manual tabulation by Test Chi square independence criteria, reached the following conclusions: The 63.9% (36) of nurses surveyed were single, 52.8% (19) have children in their employment status 63.9% (23) are employed, 52.8% (19) are paid less than s/. 1000 ($. 380) and as for his years of practice the 63.9% (23) are laboring under 5 years. Also presenting a mild stress level at a rate of 36.1% (13) and high with a 33.3% (12) so that in the present study found significant relationships between the variables: biosociolaborales factors (marital status, remuneration) and stress